TINGKAT KEPUASAN DAN LOYALITAS KONSUMEN RUMAH TANGGA DALAM MENGONSUMSI BIHUN JAGUNG DI BANDAR LAMPUNG - Riska Widyasari; Fembriarti Erry Prasmatiwi; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The objectives of this study are to analyze: the level of household consumers’ satisfaction, the level of household consumers’ loyalty, and factors that influence the satisfaction and loyalty on consuming corn vermicelli in Bandar Lampung.  The research was conducted in the randomly choosen 3 traditional markets and 3 modern markets in May to July 2013.  Accidental sampling method was employed to choose the sample of 60 consumers as respondents.  Methods of analysis used were Customer Satisfaction Index (CSI) for the degree of satisfaction, the pyramid of loyalty was used for the degree of consumers’ loyalty, and the logistic regression analysis for the factors that influence satisfaction and loyalty of household consumer.  The results showed that CSI value was 76.97 percent, it meant that the costumers were satisfied by corn vermicelli product. Most costumers tended to be loyal, because the number of commited buyers (with the value of 95 percent) was higher than that of switcher buyers (with the value of 3 percent).  Based on the logistic regression analysis, variables that significantly influenced costumers’ satisfaction were the length of consumption and purchase frequency.  Variables that significantly influenced on the costumers’ loyalty were age, education level, and purchase frequency.Key words: corn vermicelli, CSI, loyalty, pyramid of loyalty, satisfaction